2010
DOI: 10.1007/bf03353626
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterizations and hydrophobicity of micro/nano scaled heptadecafluorononanoic acid decorated copper nanoparticle

Abstract: Copper nanoparticle was synthesized in the presence of heptadecafluorononanoic acid by the conventional solution immersion method at room temperature from the copper plate, as a resource material. The bulk etching rate was calculated by the weight loss method. The pale green colored Cu-HDFN was characterized by Fourier transform infrared spectroscopy, UV-Visible spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy and contact angle measurements and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Additionally, the change of surface functional groups was interpreted from Fig. 2 b, where the fresh peaks at 569 cm −1 and 662 cm −1 were considered to be Cr = O and Cu–O, respectively 48 , 49 . These peaks appeared after adsorption of Cr(VI) and Cu(II) on the surface of SA/CMC-ZFN.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the change of surface functional groups was interpreted from Fig. 2 b, where the fresh peaks at 569 cm −1 and 662 cm −1 were considered to be Cr = O and Cu–O, respectively 48 , 49 . These peaks appeared after adsorption of Cr(VI) and Cu(II) on the surface of SA/CMC-ZFN.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we employ a chemical strategy to manipulate wettability, specifically a copper post-functionalization strategy with carboxylic acid. Prior works have demonstrated that this approach is effective for the preparation of highly hydrophobic surfaces on copper foils and plates [ 34 , 35 , 36 , 37 ]. In this study, we will use this approach to functionalize 3D-printed surfaces comprised of materials loaded with copper.…”
Section: Introductionmentioning
confidence: 99%
“…The peak around 1395 cm −1 is due to the presence of the aryl group. The presence of the C-H bond accounts for the peak at 2921 cm −1 [24,31]. In terms of the water contact angle, the measured average angle was 83° for pristine copper surface, 110° for the copper surface coated with Trichlorosilane (reference surface), and 169° for the superhydrophobic copper surface.…”
Section: Surface Morphologies and Chemical Compositionsmentioning
confidence: 95%